Cochlear apical morphology in toothed whales: Using the pairing hair cell—Deiters' cell as a marker to detect lesions. Issue 3 (7th June 2021) - Morell, Maria; IJsseldijk, Lonneke L.; Piscitelli‐Doshkov, Marina; Ostertag, Sonja; Estrade, Vanessa; Haulena, Martin; Doshkov, Paul; Bourien, Jérôme; Raverty, Stephen A.; Siebert, Ursula; Puel, Jean‐Luc; Shadwick, Robert E.
Abstract: The apex or apical region of the cochlear spiral within the inner ear encodes for low‐frequency sounds. The disposition of sensory hair cells on the organ of Corti is largely variable in the apical region of mammals, and it does not necessarily follow the typical three‐row pattern of outer hair cells (OHCs). As most underwater noise sources contain low‐frequency components, we expect to find most lesions in the apical region of the cochlea of toothed whales, in cases of permanent noise‐induced hearing loss. To further understand how man‐made noise might affect cetacean hearing, there is a need to describe normal morphological features of the apex and document interspecific anatomic variations in cetaceans. However, distinguishing between apical normal variability and hair cell death is challenging. We describe anatomical features of the organ of Corti of the apex in 23 ears from five species of toothed whales (harbor porpoise Phocoena phocoena, spinner dolphin Stenella longirostris, pantropical spotted dolphin Stenella attenuata, pygmy sperm whale Kogia breviceps, and beluga whale Delphinapterus leucas ) by scanning electron microscopy and immunofluorescence. Our results showed an initial region where the lowest frequencies are encoded with two or three rows of OHCs, followed by the typical configuration of three OHC rows and three rows of supporting Deiters' cells. Whenever two rows of OHCs were detected, there were usually only two corresponding rows of supporting Deiters' cells, suggesting that the number of rows of Deiters' cells is a good indicator to distinguish between normal and pathological features.